Calciphylaxis presenting in early chronic kidney disease with mixed hyperparathyroidism - Brucculeri, Michael (Dove Medical Press, 2011)
Calciphylaxis is a disabling and life-threatening complication that primarily affects patients who are dialysis dependent. Reports have grown in the literature of cases occurring in those who have advanced chronic kidney disease (pre-end-stage renal disease) or in the setting of transplantation. There are also a few reports of cases occurring in those without any form of chronic kidney disease but with primary hyperparathyroidism. This disease entity is characterized by calcification, intimal hypertrophy, and thrombosis of small vessels that result in necrotizing, nonhealing ulcers – many of which are life threatening. Although several strategies aimed at treating and preventing this affliction have been reported in the literature, the outcome for most patients with calciphylaxis remains quite poor. We describe a patient with comparatively early stage-3 chronic kidney disease who developed calciphylaxis in the setting of both primary and secondary hyperparathyroidism. Predictably, after subtotal parathyroidectomy, her wounds did not completely heal and her biochemical markers of hyperparathyroidism did not completely normalize until her underlying secondary hyperparathyroidism was treated medically. It was only after initiating cinacalcet that the patient experienced complete wound healing and resolution of her calciphylaxis. It also supports other authors’ findings that cinacalcet may be an important adjunct in the treatment of calciphylaxis.